Cut-off points to identify sarcopenia according to European Working Group on Sarcopenia in Older People (EWGSOP) definition. Issue 6 (December 2016) - Bahat, Gulistan; Tufan, Asli; Tufan, Fatih; Kilic, Cihan; Akpinar, Timur Selçuk; Kose, Murat; Erten, Nilgun; Karan, Mehmet Akif; Cruz-Jentoft, Alfonso J.
Summary: Background: The reported prevalence of sarcopenia ranges widely depending on its definition criterion. European Working Group on Sarcopenia in Older People (EWGSOP) developed a practical clinical definition and consensus diagnostic criteria. This definition recommends using normative data of the study population rather than other reference populations. Objective: We aimed to define the reference cut-off values for muscle mass, muscle strength and calf circumference in Turkey in order to improve general applicability of EWGSOP criteria. Material and methods: Healthy young adults between 18 and 39 years of age with no known chronic disease or chronic drug usage were included in our study to serve as reference population for assessing muscle mass. Community-dwelling older outpatients were prospectively recruited from the geriatrics outpatient clinics of a university hospital for assessing hand grip strength and calf circumference. Body composition was assessed by bioimpedance analysis. Muscle strength was assessed measuring hand grip strength with a Jamar hand dynamometer. The cut-off thresholds for muscle mass were defined as the mean-2SD of the values of the young reference study population; for grip strength were calculated from ROC analyses using cut-off values that predicted gait speed < 0.8 m/s; and for calf circumference were calculated from ROC analyses using cut-off values that predicted low muscle mass. Results: The young reference group included a total of 301 participants (187 male, 114 female; mean age: 26.5 ± 4.6 years). The cut-off thresholds for skeletal muscle mass indexes were 9.2 kg/m 2 and 7.4 kg/m 2 in males and females, respectively. The older community dwelling group included 406 subjects (123 male, 283 female, mean age: 76.6 ± 6.7 years). The cut-off thresholds for hand grip strength were 32 kg and 22 kg for males and females. The cut-off threshold for calf circumference was 33 cm for both males and females. Conclusions: The cut-off thresholds for muscle mass, grip strength and calf circumference were somewhat higher but comparable with other reference populations. Further worldwide studies from different nations and countries are needed to obtain better reference values.